DISSOLUTION BEHAVIOUR OF FINE-GRAINED MAGNETITE AND MAGHEMITE IN THE CITRATE-BICARBONATE-DITHIONITE EXTRACTION METHOD - van Oorschot I.H.M.; Dekkers M.J. (My University, 1999)
Mineral magnetic properties of soils and sediments are increasingly used as proxy parameters for environmental and palaeoclimate analysis. To investigate which magnetic minerals contribute to the environmental signal in the samples, chemical techniques such as the citrate-bicarbonate-dithionite (CBD) extraction method have been introduced in environmental magnetism studies. This technique is assumed to distinguish lithogenic (magnetite) from pedogenic (maghemite) mineral content in soils and sediments. Unfortunately, interpretation of the CBD extractions is not straightforward because the procedure is sometimes more suitable for distinction between grain size than for distinction between minerals. The procedure of the CBD extraction technique was investigated to determine the influence of extraction temperature and iron oxide concentration on the dissolution behaviour of the samples. Synthetic samples were extracted at three different temperatures (60°, 70° and 80°C) at similar iron oxide concentration (5 wt%), and for three different concentrations (0.1 wt%, 1 wt% and 5 wt%) at the same temperature (60°C). Our results show that a lower extraction temperature reduces the dissolution rate for all samples, while decrease in iron oxide concentration increases the dissolution rate. Thus, the parameters in the CBD procedure have a major influence on the dissolution behaviour of the samples. In practice this means that when natural samples of differing iron oxide concentration are extracted with this technique, the results of the extractions cannot be compared. Therefore, the outcome of this type of extraction experiment can only be accurately interpreted when the effect of the procedure on the dissolution behaviour is taken into account.
Keywords: METHODS; PALEOMAGNETISM; SOLUTIONS; MAGNETITE; MAGHEMITE